Serological relationship between Exobasidium vexans and Camellia sinensis - and M. SHARMA, B.N. CHAKRABORTY*, D. SENGUPTA (Indian Phytopathology, 2009)
Polyspecific and polyclonal antibodies (PAb) were raised against Exobasidium vexans and IgG were purified. The antisera of two origin were optimized through dilution of the antigen extract and of antiserum following plate trapped antigen (PTA)-ELISA formats. Enzyme dilution was kept constant at 1:10,000. Indirect ELISA could readily detect cross reactive antigens (CRA) between Darjeeling, Tocklai or UPASI varieties and E. vexans. Among these AV-2, TV-18, and UP-8 showed very high cross reactivity with polyspecific and polyclonal antibodies of E. vexans. Antiserum raised against non-pathogen (Fusarium graminearum) did not react significantly with tea leaf antigens whereas cross reaction of those tea leaf antigens with anti-TV18 antiserum gave higher absorbance. Dot-immunobinding assays were also employed for determining CRA that revealed significant varietal differences with anti-E. vexans serum. PTA-ELISA formats were used to detect E. vexans in naturally blister affected leaf tissues as well as artificially inoculated tea leaves (AV-2) by the pathogen. Antigens were prepared after every 24 h up to 12 d and were tested against PAb of E. vexans. Infection was detected as early as 72 h after inoculation. Cellular location of CRA was observed in healthy tea leaf varieties using PAb of E. vexans followed by labeling with fluorescein isothiocyanate. Cross sections of blister affected tea leaves also showed bright fluorescence showing the presence of pathogen in host.